Поглощение кислорода митохондриями гепатопанкреаса мидий в норме и при воздействии ДДТ - (:unkn) unknown (Киев : Наукова думка, 1979)
Исследовали влияние ДДТ на дыхание изолированных митохондрий мидий, а также митохондрий мидий, находившихся от 15 мин до 24 ч в морской воде, содержащей ДДТ (10⁻¹ мг/л) и витамины В-комплекса. Установлено, что ДДТ снижает дыхание митохондрий гепатопанкреаса как в опытах in vivo, так и in vitro. Совместное применение витаминов В-комплекса частично предотвращает данный эффект, что свидетельствует о возможной репарирующей роли витаминов для мембраны митохондрий, поврежденных ДДТ.
Oxygen Intake by the Mussel Hepatopancreas Mitochondria in Norm and as Affected by DDT
The effect of DDT on respiration of the isolated mussel hepatopancreas mitochondria as well as of mitochondria of mussels that were from 15 min to 24 h in sea water containing DDT (10⁻¹ mg/ml) and B-complex vitamins was studied. The mitochondria were isolated by the method of Schneider and Hogebum, their respiration was determined polarographically in the Gubler medium. DDT is established to decrease the hepatopancreas mitochondria respiration both in the in vivo and in vitro experiments. The DDT effect is based on influencing bio-membrane permiability and on disturbance of redox processes. The complex vitamins somewhat prevent this effect thus increasing the membrane resistance to the DDT action.